Moving territory in the rural settlement Sul Bonito in Itáquiraí/MS: touristic usages at Praia da Amizade - Daiane Alencar Silva; Edvaldo Cesar Moretti (Revista Brasileira de Pesquisa em Turismo, 2011)
The scope of the research is to understand rural areas and their changes since tourism upsurge. The study area is the rural settlement Sul Bonito comprising 421 families settled in 1996. Located in the municipality of Itaquiraí, Mato Grosso do Sul, this settlement is presented as a reference on production alternatives. Methodology included field work and interviews with settlers who adopted ways of production alternative to traditional farming practices. Bibliographic research allowed new insights and perceptions about the changes occurring in the countryside. As a result, an analysis on tourism upsurge in rural areas and its consequences in production in the settlement was obtained.